The Wage Effects of Employers' Associations: A Case Study of the Private Schools Sector - Pedro S. Martins (Institute of Labor Economics (IZA), 2023)
Does employers' association (EA) membership affect wages? Such effects, positive or negative, could follow from increased productivity, employer collusion, or other channels. We analyse this question drawing on matched employer-employee panel data, including time-varying EA affiliation and worker mobility. We consider the case of private schools in Portugal, 2010-2020, and its single EA, and develop a method to define the sector's scope. We find that school fixed effects reduce the EA wage premium considerably. However, such positive premium remains, especially when focusing on the key occupation of the industry (teachers) and when considering EA firms that follow firm-specific (non-EA) collective agreements. We also find that there is an EA wage premium for schools that join the EA, while the EA premium does not disappear for schools that leave the EA.
Keywords: J53; J62; L40; 330; employers organisations; worker mobility; social dialogue